(NmNOGOMERNOE [KALIROWANIE (B:s (NmETODY NAGLQDNOGO PREDSTAWLENIQ DANNYH (B/s - (Nd\JWISON(B, (NmARK l(B.s; (NkAMENSKIJ(B, (Nw(B.(Ns(B.s ((NmOSKWA (B:s (NfINANSY I STATISTIKA(B,s, 1988)
(NbIBLIOGR(B.: (NS(B. 218-232s
Keywords: (NsTATISTI^ESKIJ ANALIZ MNOGOMERNYJs